Transcendence Certificates for D-finite Functions - Kauers, Manuel; Koutschan, Christoph; Verron, Thibaut (arXiv.org, 2023)
Although in theory we can decide whether a given D-finite function is transcendental, transcendence proofs remain a challenge in practice. Typically, transcendence is certified by checking certain incomplete sufficient conditions. In this paper we propose an additional such condition which catches some cases on which other tests fail.